Challenges and Gaps in the Management of Chronic Hepatitis C Infection: Insight from A Tertiary Hospital in Indonesia - Lily Chandrawati; Cecilia Octaria Permatadewi; Hesti Triwahyu Hutami; Didik Indiarso; Hery Djagat Purnomo (The Indonesian Society for Digestive Endoscopy, 2026)
Background: Hepatitis C virus (HCV) infection remains a significant public health burden in Indonesia, affecting approximately 2.5 million people. The introduction of direct-acting antivirals (DAAs) has revolutionized HCV management by offering highly effective and well-tolerated treatment options. Since 2017, Indonesia has implemented an HCV cascade of care and a government-funded DAA program to support the World Health Organization (WHO) goal of HCV elimination by 2030. However, challenges in diagnostic accessibility and treatment follow-up continue to hamper progress. This study aims to evaluate the implementation of the HCV cascade of care at Dr. Kariadi General Hospital, Semarang, Indonesia.Methods: A retrospective descriptive study was conducted at Dr. Kariadi General Hospital, which included data from patients who tested positive for anti-HCV antibodies between January 2019 and November 2024. HCV treatment was categorized into five stages: (1) positive anti-HCV antibody test, (2) HCV RNA test, (3) positive HCV RNA result, (4) treatment initiation, and (5) sustained virologic response 12 weeks post-treatment (SVR12). Data analysis was performed using SPSS Statistics version 26. Categorical variables were expressed as frequencies and percentages, and findings were presented as numbers and proportions across each stage of the care cascade.Results: Among 317 patients with positive anti-HCV antibody results (55% men, 45% women; median age: 56 years), 280 (88%) underwent HCV RNA testing, and 213 (76%) were confirmed positive. Of these, 185 patients (87%) initiated treatment, 144 (78%) completed therapy, and 108 (75%) achieved SVR12.Conclusion: This study shows that significant gaps remain at various stages of the HCV care cascade, particularly in confirmatory HCV RNA testing, treatment initiation, and post-treatment follow-up.